Does Foreign Bank Penetration Reduce Access to Credit in Developing Countries? Evidence from Asking Borrowers - Clarke, George R.G.; Cull, Robert; Martinez Peria, Maria Soledad (World Bank, Washington, DC, 2014)
Existing evidence on the effect of foreign bank penetration on lending to small and medium-size enterprises is ambiguous. Case studies of developing countries show that foreign banks lend less to such firms than domestic banks do. But cross-country studies find that foreign bank entry fosters competition and reduces interest rates, benefits that should extend to all firms. The authors use data from a large cross-country survey of enterprises to investigate this issue. Their results suggest that foreign bank penetration improves financing conditions (both the quantities of financing and the terms) for enterprises of all sizes, although it seems to benefit larger firms more.